Properties and temperature evolution of the spectrum of localized quasi-particles interacting with polarization phonons in two models - Tkach, M.V.; Seti, Ju.O.; Voitsekhivska, O.M.; Pytiuk, O.Yu. (Condensed Matter Physics, 2016)
Using the Feynman-Pines diagram technique, the energy spectrum of localized quasi-particles interacting with
polarization phonons is calculated and analyzed in the wide range of energies at the finite temperature of
the system. It is established that the general model of the system, besides the bound states known from the
simplified model with an additional condition for the operator of quasi-particles number, contains the new
bound states even for the systems with weak coupling. The contribution of multi-phonon processes into the
formation of renormalized spectrum of the system is analyzed. The reasons of the appearance, behaviour and
disappearance of separate pairs of bound states depending on the coupling constant and temperature are
revealed. Методом дiаграмної технiки Фейнмана-Пайнса розраховано i дослiджено енергетичний спектр локалiзованих квазiчастинок, взаємодiючих з поляризацiйними фононами у широкiй областi енергiй при скiнченнiй температурi системи. Показано, що загальна модель системи крiм зв’язаних станiв, вiдомих зi
спрощеної моделi з накладеною додатковою умовою на оператор повного числа квазiчастинок, навiть
зi слабким зв’язком мiстить новi зв’язанi стани. Виявлена роль багатофононних процесiв у формуваннi перенормованого спектру системи. Встановлено причини появи, еволюцiї та зникнення окремих пар
зв’язаних станiв у залежностi вiд величини енергiї зв’язку та температури.